Evaluation of the Potential of Self-Nanoemulsifying Drug Delivery System (SNEDDS) in Increasing Oral Bioavailability of Low-Solubility Drugs - Muhammad Nurul Fadel; Emma Jayanti Besan; Dzukharian Munandar; Husnunnisa; Cut Intan Annisa Puteri (CV. Get Press Indonesia, 2026)
Losartan potassium, a Biopharmaceutics Classification System (BCS) Class II drug, exhibits poor aqueous solubility and limited oral bioavailability. This study aimed to develop and optimize a Self-Nanoemulsifying Drug Delivery System (SNEDDS) to enhance its dissolution and absorption. SNEDDS formulations were prepared using Capmul MCM C8, Tween 80, and PEG 400 based on solubility screening and ternary phase diagram analysis. The optimized formulation (F3) was evaluated for droplet size, polydispersity index (PDI), in vitro drug release, pharmacokinetics, and stability. Pharmacokinetic studies were conducted in experimental rats Pharmacokinetic studies were conducted in experimental rats (n = 3 per group) to assess bioavailability. The optimized SNEDDS produced nanoemulsions with a droplet size of 68.3 nm, low PDI, and good dilution stability. In vitro studies demonstrated rapid drug release (>96% within 30 minutes), significantly higher than the plain suspension. Pharmacokinetic results showed a 3.09-fold increase in bioavailability and a 2.79-fold increase in Cmax without altering Tmax. Stability studies confirmed good physicochemical stability over six months under ICH conditions. In conclusion, SNEDDS is a promising strategy to improve the oral bioavailability of poorly water-soluble drugs such as losartan potassium.